Proteínas totais e clorofila-A no material particulado em suspensão de um igarapé amazônico - RIBEIRO, Irla Ramos (2019)
Proteins are biomolecules belonging to the tissues of aquatic organisms and their study brings new approaches to the study of the quality of water bodies. Therefore, this work aims to contribute to the evaluation of the biochemical composition of the suspended particulate matter of an Amazonian anthropic igarapé based on the concentrations of total proteins and chlorophyll a. For this study, surface water was collected from the Tucunduba Igarapé. This igarapé suffers impacts due to the urbanization and disordered occupation of the city of Belém, being one of the main receivers of untreated sewage. In the laboratory the extraction of the chlorophyll compounds and total proteins of the suspended particulate material was carried out. In the results, protein concentrations were obtained between 2,297-0,028 (μg/mL), chlorophyll-a between 3.8-0.9 (μg/L) and feofitin-a between 4.5-15.0 (μg/L), in which it was possible to observe that the concentrations of total proteins do not suffer direct influence of the chlorophyll compounds, but possibly of the antropic action.